2020
DOI: 10.3390/genes11090983
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Modulate the Pathogenesis of Alzheimer’s Disease: An In Silico Analysis in the Human Brain

Abstract: MicroRNAs (miRNAs) are small RNAs involved in the post-transcriptional regulation of their target genes, causing a decrease in protein translation from the mRNA. Different miRNAs are found in the nervous system, where they are involved in its physiological functions, but altered miRNAs expression was also reported in neurodegenerative disorders, including Alzheimer’s disease (AD). AD is characterized by memory loss, cognitive function abnormalities, and various neuropsychiatric disturbances. AD hallmarks are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…In particular, miR-199 levels increase during early brain development and modulate extracellular signal-regulated kinase (ERK) [ 76 ]. Intriguingly, an in silico analysis reported that AD patients’ brains present upregulated levels of miR-199 [ 78 ]. Song et al, showed that miR-199 was involved in the development of AD by decreasing the expression of neuritin, a protein involved in neural development and plasticity [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, miR-199 levels increase during early brain development and modulate extracellular signal-regulated kinase (ERK) [ 76 ]. Intriguingly, an in silico analysis reported that AD patients’ brains present upregulated levels of miR-199 [ 78 ]. Song et al, showed that miR-199 was involved in the development of AD by decreasing the expression of neuritin, a protein involved in neural development and plasticity [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the results of this study demonstrated increased ReHo in the left BA21, which is located in the temporal cortex and involved in auditory and language processing. 37 Previous studies have demonstrated concurrent links between motor skills and auditory/language development in children. 38,39 Furthermore, the auditory/ language information has been shown to be involved in the regulation of sensorimotor function.…”
Section: Alteration Of Sensory Motor Related Brain Regionsmentioning
confidence: 99%
“…Thus, in general, given their important role in finely tuning post-transcriptional expression of proteins involved in synaptic plasticity, microRNAs might be central targets in the analysis/therapy of learning and memory processes, neurological diseases and dementia [ 56 , 225 , 235 , 236 , 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 ].…”
Section: Post-transcriptional Regulation and Synaptic Plasticity In T...mentioning
confidence: 99%